A study on the awareness of violence against women among citizens in Kota Bharu / Nur Raudah Ruzelan , Nurul Shahira Samsudin and Nur Aliya Mohamad Azemi - Ruzelan, Nur Raudah; Samsudin, Nurul Shahira; Mohamad Azemi, Nur Aliya (2019)
Violence against women (VAW) is a serious human rights violation. Its impact ranges from immediate to long-term multiple physical consequences, sexual and mental, including death. This paper presents the awareness among citizens towards VAW for their concern about violence, perception, and knowledge about violence. The research was carried out using a sample questionnaire consisting of 384 Kota Bharu citizens. The samples were selected using a multi-stages clustering sampling method. Independent t-test used to determine the difference mean in awareness between gender and it is found that there is no difference mean in awareness of VAW between male and female. One-way ANOVA used to see if there is any significant difference mean in their awareness of VAW between demographic factors included education levels and sub-districts. The research found that there is no difference mean between demographic factors in the awareness of VAW. Structural Equation Modelling (SEM) used to analyse the effects of citizens' concerns, knowledge, and public‟s perception towards awareness of VAW. The finding indicates that concern, knowledge, and perception have a significant impact on the awareness of VAW. The institute can provide citizens with more information to give them better concern, knowledge and public‟s perception. With appropriate education, it is important to increase awareness and knowledge of this abuse